Principle 5 C in The Practice of Peer to Peer Lending (P2P) Financial Technology in The Perspective of Business Ethics and Islamic Justice - Hesti Dwi Astuti; Cucu Sholihah; Mualimin Mochammad Sahid; Abu Umar Faruq Ahmad; Yayan Sopyan; Uus Ahmad Husaeni (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
Non-bank financial service actors in the era of the COVID-19 pandemic made a breakthrough by creating fintech (Financial technology) through the development of Peer Peer Lending (P2P) or online loans. The purpose of this study is to analyze the implementation of 5C principles in the practice of peer-to-peer lending Fintech based on a review of Islamic business ethics. The method used in this research is a normative juridical approach with a descriptive research approach. The data that has been obtained will be arranged systematically for further qualitative analysis. This study concludes that principles and business ethics must be considered with the concept of â€œThe Five Câ€™s Principle of Credit Analysisâ€ in either conventional or sharia systems. In the case of customers who choose a sharia online loan system, they must also pay attention to the ethical aspects of financial business in Islam, which is something that must be considered considering that in Islam, ethical issues are related to the determination of economic policies that will affect the halalness of service and the agreement of the parties.Â